Methodical Approach for the Detection of Pesticides in Groundwater - a Swiss Example - Kozel, Ronald; Zwahlen, François (: Birkhauser Verlag Ag, 1993)
A methodical approach for the detection of pesticides in porous aquifers is summarised and illustrated on the basis of a regional study. The process is mainly based on a sound knowledge of the three following elements: the hydrogeologic environment, data on the use of pesticide products and data on the behaviour of the pesticides in the soil and at deeper levels.
Keywords: GROUNDWATER; POLLUTION; PESTICIDES; METHODOLOGY; DETECTION OF POLLUTANTS